Life-Cycle Cost Analysis of a 220Ah Tubular Battery in a Solar-Powered Academic Setting - Obiora Jeremiah Obiafudo; Godspower Onyekachukwu Ekwueme; Ugochukwu Richards Orji; Clement Nworji Obiora (Journal Majelis Paspama, 2025)
Reliable energy storage remains a critical challenge in sustaining solar-powered systems within academic environments, particularly in Nigeria where erratic grid supply hinders teaching and research activities. Batteries constitute the most cost-intensive component of solar installations, and their economic performance determines long-term viability. The study integrated MATLAB/Simulink simulations, field observations, and expert input. The analysis followed three stages: system modeling, performance evaluation, and economic benchmarking. Monocrystalline PV modules (220–330 W, 18–20% efficiency) were configured with 7° tilt and passive cooling to optimize performance in Nigeria’s tropical climate. A 60A MPPT controller and 1 kW inverter enhanced efficiency, while protections improved system reliability. Life-cycle cost analysis (LCCA) over 15 years at 10% discount rate compared tubular lead-acid and LiFePO₄ batteries, revealing LiFePO₄’s long-term cost advantage. Sensitivity analysis and benchmarking confirmed its superior cycle life, reduced maintenance, and lower levelized storage costs. The life-cycle cost analysis showed that tubular lead-acid batteries were cheaper upfront (₦92,000/kWh vs. ₦230,000/kWh) but incurred higher O&M (₦46,000/kWh every 5 years) and required replacements at years 5 and 10, raising their 15-year cost to ₦400,200/kWh. LiFePO₄, though costlier (₦481,100/kWh total), offered longer lifespan, lower O&M (₦18,400/kWh), and higher salvage value (₦34,500). Net Present Cost was lower for tubular (₦248,500/kWh vs. ₦289,200/kWh), yet LiFePO₄ delivered a better Levelized Cost of Storage (₦98/kWh vs. ₦127/kWh) and achieved payback in 8.2 years. Thus, tubular favored affordability, while LiFePO₄ provided superior long-term value and reliability for Nigerian universities. The study recommends a shift toward durable storage technologies to enhance reliability, reduce operating costs, and strengthen energy security in Nigerian universities.